Cultural Adjustment and Social Justice Behaviour: The Role of Individual Differences in Multicultural Personality. Issue 6 (November 2016) - Fietzer, Alexander W.; Ponterotto, Joseph G.; Jackson, Margo A.; Bolgatz, Jane
The present study examined altruistic behaviour using broad personality traits (the Big Five) and the narrow personality trait of cultural adjustment (multicultural personality) while controlling for social justice attitudes and other demographic variables. Using an analogue version of a modified dictator game, 153 participants were required to divide a variable amount of money between themselves and a hypothetical recipient who was treated unfairly in a prior dictator game (based on results from a separate sample). We varied the race (Black and White) and gender (male and female) of the fictional recipient to present the individual as either advantaged or disadvantaged in society. Participants were randomly assigned to one of three conditions with the recipient presented as (i) a White man, (ii) a White woman, or (iii) a Black man. A separate sample of 71 participants rated recipients as treated unfairly and as representing a marginalized group. Results showed that subscales of the Multicultural Personality Inventory predicted giving behaviour above and beyond the variance accounted for by broad personality traits and attitudes towards social justice. The discussion focuses on implications for research in social justice based on cultural adaptation and personality. Copyright © 2016 European Association of Personality Psychology